2017
DOI: 10.4018/ijisscm.2017100101
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Coordination through a Revenue-Sharing Contract with Two Kinds of Fuzzy Demand

Abstract: Revenue-sharing contract is used in many industries. However, it is hard to guarantee that the retailer report the sales truly to the supplier. In fact, the retailer has both incentive and opportunity to underreport the sales to reduce the sharing revenue to the supplier. What the supplier should do when meeting with the opportunistic retailer(s)? This paper studies a kind of opportunistic phenomenon in a supply chain in which a supplier sells to a retailer under a revenue-sharing contract. Two settings are di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
(5 reference statements)
0
10
0
Order By: Relevance
“…Bi, He, and Luo et al (2013) demonstrated that a sales-rebate contract regarding fairness broadens the voluntary cooperation prospects and increases the overall profit of the supply chain [ 33 ]. Some other coordinating contracts with fairness concerns have also been fully characterized in different contexts, such as revenue-sharing contracts (Li Q et al [ 29 ]; Wang X et al [ 34 ]; Pu X J et al [ 35 ]) and buy-back contracts (Wei G et al [ 36 , 37 ]). Although these articles considered more complex issues, the majority of them also simplified the functions that characterize fairness concerns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bi, He, and Luo et al (2013) demonstrated that a sales-rebate contract regarding fairness broadens the voluntary cooperation prospects and increases the overall profit of the supply chain [ 33 ]. Some other coordinating contracts with fairness concerns have also been fully characterized in different contexts, such as revenue-sharing contracts (Li Q et al [ 29 ]; Wang X et al [ 34 ]; Pu X J et al [ 35 ]) and buy-back contracts (Wei G et al [ 36 , 37 ]). Although these articles considered more complex issues, the majority of them also simplified the functions that characterize fairness concerns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, alignment of individual objectives of SC agents in a multi-echelon SC is more complicated (Sang, 2016a, b). As two adjacent agents choose their contractual agreement independently and separately, determining coordination strategy for a multi-echelon SC becomes more complex (Wang et al. , 2014; Zhao et al.…”
Section: Introductionmentioning
confidence: 99%
“…Such contracts can be summarized to include quantity flexibility contracts, backup agreements, buy-back or return policies, incentive mechanisms and revenue sharing contracts. Wang, Zhao and Tang (2008) focus on revenue-sharing in a supply chain with one retailer and one supplier considering fuzzy demand. Wang, Zhao and Tang (2008) consider two kind of fuzzy demand: iso-price elastic demand and linear demand.…”
mentioning
confidence: 99%
“…Wang, Zhao and Tang (2008) focus on revenue-sharing in a supply chain with one retailer and one supplier considering fuzzy demand. Wang, Zhao and Tang (2008) consider two kind of fuzzy demand: iso-price elastic demand and linear demand. They conclude by stating that future work considering more complex fuzzy demands should be considered.…”
mentioning
confidence: 99%